Determining the velocity required for skin perforation by fragment simulating projectiles: a systematic review. Issue 4 (3rd June 2013) - Breeze, John; Clasper, JC
Abstract : Introduction: Explosively propelled fragments are the most common cause of injury to soldiers on current operations. Researchers desire models to predict their injurious effects so as to refine methods of potential protection. Well validated physical and numerical models based on the penetration of standardised fragment simulating projectiles (FSPs) through muscle exist but not for skin, thereby reducing the utility of such models. Method: A systematic review of the literature was undertaken using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology to identify all open source information quantifying the effects of postmortem human subject (PMHS) and animal skin on the retardation of metallic projectiles. Projectile sectional density (mass over presented cross-sectional area) was compared with the velocity required for skin perforation or penetration, with regard to skin origin (animal vs PMHS), projectile shape (sphere vs cylinder) and skin backing (isolated skin vs that backed by muscle). Results: 17 original experimental studies were identified, predominantly using skin from the thigh. No statistical difference in the velocity required for skin perforation with regard to skin origin or projectile shape was found. A greater velocity was required to perforate intact skin on a whole limb than isolated skin alone (p<0.05). An empirical relationship describing the velocity required to perforate skin by metallic FSPs of a range of sectional densities was generated. Discussion: Skin has a significant effect on the retardation of FSPs, necessitating its incorporation in future injury models. Perforation algorithms based on animal and PMHS skin can be used interchangeably as well as spheres and cylinders of matching sectional density. Future numerical simulations for skin perforation must match the velocity for penetration and also require experimental determination of mechanical skin properties, such as tensile strength, strain and elasticity at high strain rates.